Life history and large-scale habitat use of brown trout (Salmo trutta) and brook trout (Salvelinus fontinalis) - Öhlund, Gunnar (2006)
Over the years, several salmonid species have been widely spread and successfully introduced all over the world. In Sweden, introduced brook trout (Salvelinus fontinalis) has been successful in establishing a substantial number of new populations, a fact that has raised concerns about indigenous brown trout (Salmo trutta) populations being outcompeted. The competitive relationships of introduced and native salmonids have received much scientific attention, yet most studies have failed to reveal the specific mechanisms by which species interact. A powerful way of dealing with interspecific competition is measuring of species-specific changes in fitness over environmental and biotic gradients, an approach that requires accurate measurements of life historical metrics. I compared the expression of life history traits in stream resident populations of 1) sympatric brook trout and brown trout, 2) allopatric and sympatric brown trout. This information was complemented by a survey on patterns of distribution and density of the two species on a larger geographical scale, covering various environmental gradients. The comparisons of sympatric and allopatric brown trout indicated that brown trout life history was effected by brook trout presence in terms of lower growth rate, delayed maturation and increased apparent mortality. The life history of brook trout was clearly shorter than that of brown trout, with higher growth rate, earlier maturation, higher fecundity and higher mortality. Data from the Swedish Electrofishing Register indicates that brown trout in many cases can withstand competition from brook trout. It should be remembered that very small streams where brook trout is most likely to be competitively dominant, probably are underrepresented in the database. Still, it seems as though certain stream characteristics are required for competitive exclusion of brown trout to occur. With stream size and productivity as the main features structuring interactions between the two salmonids, combinations of other factors like temperature, level of structural heterogeneity, amount of pools and deeper habitats and possibilities for female migration seem important on a spatially smaller scale. I suggest that behavioral differences in combination with the above factors, might gradually decrease the ability of brown trout to withstand competition from brook trout as stream-size and/or productivity declines